Rahnella sp., a Dominant Symbiont of the Core Gut Bacteriome of Dendroctonus Species, Has Metabolic Capacity to Degrade Xylan by Bifunctional Xylanase-Ferulic Acid Esterase - Pineda-Mendoza, Rosa María; Zúñiga, Gerardo; López, María Fernanda; Hidalgo-Lara, María Eugenia; Santiago-Hernández, Alejandro; López-López, Azucena; Orduña, Flor N. Rivera; Cano-Ramírez, Claudia (Frontiers in Microbiology, 2022)
Rahnella sp. ChDrAdgB13 is a dominant member of the gut bacterial core of species of the genus Dendroctonus, which is one of the most destructive pine forest bark beetles. The objectives of this study were identified in Rahnella sp. ChDrAdgB13 genome the glycosyl hydrolase families involved in carbohydrate metabolism and specifically, the genes that participate in xylan hydrolysis, to determine the functionality of a putative endo-1,4-β-D-xylanase, which results to be bifunctional xylanase–ferulic acid esterase called R13 Fae and characterize it biochemically. The carbohydrate-active enzyme prediction revealed 25 glycoside hydrolases, 20 glycosyl transferases, carbohydrate esterases, two auxiliary activities, one polysaccharide lyase, and one carbohydrate-binding module (CBM). The R13 Fae predicted showed high identity to the putative esterases and glycosyl hydrolases from Rahnella species and some members of the Yersiniaceae family. The r13 fae gene encodes 393 amino acids (43.5 kDa), containing a signal peptide, esterase catalytic domain, and CBM48. The R13 Fae modeling showed a higher binding affinity to ferulic acid, α-naphthyl acetate, and arabinoxylan, and a low affinity to starch. The R13 Fae recombinant protein showed activity on α-naphthyl acetate and xylan, but not on starch. This enzyme showed mesophilic characteristics, displaying its optimal activity at pH 6.0 and 25°C. The enzyme was stable at pH from 4.5 to 9.0, retaining nearly 66–71% of its original activity. The half-life of the enzyme was 23 days at 25°C. The enzyme was stable in the presence of metallic ions, except for Hg2+. The products of R13 Fae mediated hydrolysis of beechwood xylan were xylobiose and xylose, manifesting an exo-activity. The results suggest that Rahnella sp. ChDrAdgB13 hydrolyze xylan and its products could be assimilated by its host and other gut microbes as a nutritional source, demonstrating their functional role in the bacterial-insect interaction contributing to their fitness, development, and survival.